Соціокультурна ідентичність як чинник підвищення ефективності політичного управління - Малінін, В. В.; Малинин, В. В.; Malinin, V. (My University, 2013)
The article discusses the socio-cultural identity, its place and role in the implementation of government policy and the implementation of basic democratic principles of governance. Determined that the socio-cultural identity serves an important factor in improving the efficiency of public administration in modern conditions.
Малінін В. В. Соціокультурна ідентичність як чинник підвищення ефективності політичного управління / В. В. Малінін // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 258-267.
Keywords: соціокультурна ідентичність; державна політика; демократичні принципи державного управління; социокультурная идентичность; государственная политика; демократические принципы государственного управления; social and cultural identity; public policy; the democratic principles of governance